The effects of probiotics on renal function and uremic toxins in patients with chronic kidney disease; a meta-analysis of randomized controlled trials - Charat Thongprayoon; Spencer T. Hatch; Wisit Kaewput; Konika Sharma; Patompong Ungprasert; Karn Wijarnpreecha; Matthew D'Costa; Michael A Mao; Wisit Cheungpasitporn (Society of Diabetic Nephropathy Prevention, 2018)
Context: There is mounting evidence suggesting bidirectional crosstalk between microbiota and host. However, the effects of probiotics on renal function and uremic toxins in chronic kidney disease (CKD) patients are unclear. Evidence Acquisitions: A literature review was conducted using MEDLINE, EMBASE, and Cochrane Database of Systematic Reviews from inception through November 2017 to identify randomized controlled trials (RCTs) assessing the effects of probiotics on renal function and uremic toxins in CKD patients. Effect estimates from the individual studies were extracted and combined using fixed-effect meta-analysis with inverse variance weights. Results: Five RCTs with 161 CKD patients were enrolled. Compared to controls, there were no significant differences in serum creatinine and estimated glomerular filtration rate (eGFR) after post-probiotic course (4 weeks to 6 months) with standardized mean differences (SMDs) of 0.01 (95% CI -0.29 to 0.30) and -0.01 (95% CI -0.43 to 0.41), respectively. Compared to the controls, p-cresol levels were significantly reduced after treatment with probiotics with SMD of -0.61 (95% CI -1.04 to -0.19). No significant infectious complications were noted during treatment with probiotics in CKD patients. Conclusions: Based on the findings of our meta-analysis, there are no significant changes in serum creatinine or eGFR after short-term treatment with probiotics, when compared to controls. However, our meta-analysis suggests potential beneficial effects of probiotics on uremic toxins in CKD patients. Future studies are required to assess its long-term effects on CKD progression and uremic toxins.